Myoxocephalus jaok ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Myoxocephalus jaok (Cuvier, 1829). Plain Sculpin. To 75 cm (29.5 in) TL (Spies et al. 2012). Seas of Japan and Okhotsk to western and eastern Bering Sea to western Beaufort Sea at least to 71°15’N, 153°07’W to eastern Aleutian Islands, and Limestone Inlet, south-eastern Alaska (Mecklenburg et al. 2016). Benthic; depth: intertidal to 680 m (2,231 ft) (min.: Mecklenburg et al. 2016; max.: Sheiko and Fedorov 2000). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 123, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...